Correlations Between Sea‐Level Components Are Driven by Regional Climate Change. Issue 2 (23rd February 2021) - Lambert, Erwin; Le Bars, Dewi; Goelzer, Heiko; van de Wal, Roderik S.W.
Abstract: The accurate quantification of uncertainties in regional sea‐level projections is essential for guiding policy makers. As climate models do not currently simulate total sea level, these uncertainties must be quantified through summation of uncertainties in individual sea‐level components. This summation depends on the correlation between the components, which has previously been prescribed or derived from each individual component's dependence on global mean surface temperature. In this study, we quantify, for the first time, regional correlations between sea‐level components based on regional climate change projections. We compute regional sea‐level projections consistent with climate projections from an ensemble of 14 Earth System Models. From the multi‐model spread, we estimate the uncertainty in the regional climate's response to greenhouse forcing. To quantify the total uncertainty, we add the uncertainty in the response of sea‐level components to this regional climate change. This approach reveals how regional climate processes impose correlations between sea‐level components, affecting the total uncertainty. One example is an anti‐correlation between North Atlantic sterodynamic change and Antarctic dynamic mass loss, suggesting a teleconnection established by the large‐scale ocean circulation. We find that prescribed correlations, applied in the fifth assessment report of the Intergovernmental Panel on Climate Change, lead to a global overestimation in the uncertainty in regional sea‐level projections on the order of 20%. Regionally, this overestimation exceeds 100%. We conclude that accurate uncertainty estimates of regional sea‐level change must be based on projections of regional climate change and cannot be derived from global indicators such as global mean surface temperature. Plain Language Summary: Projections of future sea‐level rise come with a great uncertainty. To inform policy makers, it is essential to accurately quantify the uncertainty in regional sea‐level rise. This is difficult, as climate models do not simulate all processes that contribute to sea‐level rise. In this study, we have developed a new method to quantify the uncertainty in regional sea‐level rise, which is consistent with climate projections from a set of 14 climate models. We conclude that a number of processes in the climate system link together the different sea‐level components. This interdependency affects the uncertainty in future projections. This interdependency was previously accounted for in the fifth assessment report of the Intergovernmental Panel on Climate Change. Here, we find that their method leads to an overestimation of uncertainties which are on the order of 20% globally. Regionally, uncertainties are overestimated by more than 100%. Altogether, we conclude that regional climate processes must be accounted for in order to accurately quantify the uncertainty in future sea‐level projections. Key Points: We have computed regional sea‐level projections, consistent with regional climate projections from an ensemble of Earth System Models Regional climate processes impose correlations between sea‐level components that cannot be derived from global mean surface temperature Correlations prescribed in the IPCC's fifth assessment report lead to overestimated projection uncertainties exceeding 100% regionally